(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The adoption of renewable energy is accelerating globally in wind and solar energy generation, solar energy particularly provides the promising outlook, its availability and flexibility of use makes it the most acceptable energy source required to achieve high perceptions of intermittent renewable energy. Despite this, solar energy storage capacity is currently underutilized in terms of minutes to hours of output at full power capacity. Although, research efforts and resource planning have begun to forecast on large-scale solar energy storage for a long duration, none has achieved a larger power capacity for a long duration. To this end, we explored the essentials of long-duration energy storage systems by analysing energy density, cycle durability and capacity rating for Hybrid Lithium-ion Battery (LiFePO4). In doing so, major components of potential long-duration storage values and their sensitivity to key parameters were assessed and the resulting indicators compared. The study showed a fast response time with improved energy density leading to a relatively high efficiency of about 42% as compare to the standard roundtrip efficiency of 45%. Cycle durability was highly influenced by depth of discharge (DoD), leading to a relatively short 3.5-hour lifetime for charge management, which is common when considering typical battery behaviour. Thus, strategies identified to improve Li-ion batteries: finding alternative electrode materials to improve energy density, decrease the environmental and societal impact of the raw materials, implementing self-healing mechanisms to improve cycle lifetime, and improving the efficiency to decrease costs.